Association Between Dietary Fiber Intake and All-Cause and Cardiovascular Mortality in Middle Aged and Elderly Adults With Chronic Kidney Disease - Kwon, Yu-Jin; Lee, Hye Sun; Park, Go Eun; Lee, Ji-Won (Frontiers in Nutrition, 2022)
Background and Aims Despite accumulating evidence on the benefits of dietary fiber in the general population, there is a lack of representative data on mortality in patients with chronic kidney disease (CKD). This study examined the role of dietary fiber intake on all-cause and cardiovascular mortality in patients with CKD using representative Korean cohort data. Methods The study included 3,892 participants with estimated glomerular filtration rates <60 mL/min/1.73 m2 from the Korean Genome and Epidemiology Study. Mortality status was followed by data linkage with national data sources. Nutritional status was assessed using a validated food frequency questionnaire. Dietary fiber was categorized into quintiles (Q). A multivariable Cox proportional hazards regression model was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for all-cause and cardiovascular mortality. Results The average daily fiber intake of patients with CKD was 5.1 g/day. During the 10.1-year follow-up period, 602 (149 cardiovascular) deaths were documented. The HR (95% CI) for all-cause mortality in the highest quintile compared with that in the lowest quintile was 0.63 (0.46–0.87) after adjusting for age, sex, BMI, smoking, alcohol intake, exercise, total calorie intake, hypertension, diabetes, and dyslipidemia (P = 0.005). The HR (95% CI) for cardiovascular mortality in the highest quintile compared with that in the lowest quintile was 0.56 (0.29–1.08) after adjusting for same confounders (P = 0.082). Conclusion In conclusion, we observed an inverse association between dietary fiber intake and all-cause mortality in CKD patients. Small increments in fiber intake reduced the risk of all-cause mortality by 37%. This finding highlights the need for inexpensive but important dietary modification strategies for encouraging fiber intake in the Korean CKD population.